Valores e cultura organizacionais e seus impactos na anomia organizacional: o teste de um modelo explicativo - Lima, Ingrid Ferreira de (2020)
The literature shows the need to intensify investigations of anomie in the organizational context in order to create more stable environments in which norms and values work and guide the behavior of employees, in addition to benefits for organizations. In this approach, the present study aimed to test a model in which organizational anomie is explained by the perception of organizational values and organizational culture (dimension of organizational practices) in a sample of workers linked to public health organizations (Primary Health Care) of four municipalities in the Triângulo Mineiro region. The sample consisted of 208 workers from Family Health Strategy (FHS) units, with temporary and effective work links. After the workers' consent to participate in the research, data collection was performed with reliable and valid instruments, which were analyzed using descriptive statistics and multiple hierarchical regression (enter method), with organizational anomie as the criterion variable. Among the results, it was found that the average of the responses of the servers in the Organizational Anomy Scale (EAO) remained close to the midpoint of the scale. The value most perceived by workers was compliance, although it was not related to organizational anomie. The model test showed that organizational values explained 34% of the criterion variable variance, and organizational practices explained only 0.6% of the criterion variable variance. The conclusions indicate that the proposed model has not been confirmed, revealing that the organizational values proved to be a better predictor of organizational anomie than the organizational practices. Research that verifies organizational justice and values as a predictor of organizational anomie is recommended, as well as investigating the influence of organizational anomie on organizational moral values and virtues.